2000
DOI: 10.1211/0022357001774057
|View full text |Cite
|
Sign up to set email alerts
|

SM-20220, a Potent Na+/H+ Exchange Inhibitor, Improves Consciousness Recovery and Neurological Outcome Following Transient Cerebral Ischaemia in Gerbils

Abstract: We studied the cerebroprotective effect of SM-20220 (N-(aminoiminomethyl)-1-methyl-1H-indole-2-carboxamide methanesulphonate), a newly synthesized Na+/H+ exchanger (NHE) inhibitor, in Mongolian gerbil global ischaemia. Transient cerebral ischaemia was induced by clipping both common carotid arteries for 30 min followed by 24h reperfusion. Intravenous administration of SM-20220 (0.3 or 1.0 mg kg(-1)) immediately after reperfusion significantly shortened the consciousness recovery time (P < 0.01). SM-20220 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…SM-20220 reduced the extent of hypoxia-reoxygenation injury in cultured neurons and glia (7). Furthermore, SM-20220 improves neurological outcome and survival rate (8) and may be a potential therapy for the treatment of acute stroke. Brain tissue consumes extremely high levels of oxygen and glucose, and maintenance of the cerebral blood flow is a prerequisite *Corresponding author.…”
Section: /Hmentioning
confidence: 98%
“…SM-20220 reduced the extent of hypoxia-reoxygenation injury in cultured neurons and glia (7). Furthermore, SM-20220 improves neurological outcome and survival rate (8) and may be a potential therapy for the treatment of acute stroke. Brain tissue consumes extremely high levels of oxygen and glucose, and maintenance of the cerebral blood flow is a prerequisite *Corresponding author.…”
Section: /Hmentioning
confidence: 98%
“…2,10,18,19) Our previous study showed that SM-20220 prevented the infarction in a rat transient MCA occlusion model 10,11) ; however, the relationship between the timing of drug administration and its beneficial effects was not clear. In the present study, we investigated the dependence of the effect of SM-20220 on infarct size on the dose and on the timing of drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…10) Furthermore, SM-20220 improved the neurological outcome and survival rate in gerbil stroke models. 11) These results suggest that the NHE inhibitor may represent a new class of drugs for the treatment of ischemic brain injury. In this study, we used a rat transient stroke model to investigate the relationship between the neuroprotective effect of SM-20220 and the timing of its administration.…”
mentioning
confidence: 93%
“…Yorkshire-Duroc pigs treated with cariporide (HOE 642), a potent and selective inhibitor of NHE-1, at the onset of a 90 min deep hypothermic circulatory arrest demonstrated improved neurologic recovery (Castellá et al, 2005). Similarly, inhibition of NHE-1 with N-[aminoiminomethyl]-1-methyl-1H-indole-2-carboxamide methanesulfonate (SM-20220) improved neurologic function in a gerbil model of transient global cerebral ischemia (Kuribayashi et al, 2000). Administration of the NHE-1 inhibitor ethylisopropylamiloride (EIPA) prior to bilateral carotid artery occlusion in gerbils resulted in decreased hippocampal neuronal cell death and improved neurologic function (Phillis et al, 1999).…”
Section: Global Ischemiamentioning
confidence: 99%
“…The IC 50 for the human NHE-1 are as follows: Amiloride = 10.7 µM, Cariporide = 0.08 µM, T-165229 = 13 nM. Importantly, the NHE inhibitors HOE 642 and SM-20220 not only reduce cell death and edema, but also improve neurological function in in vivo ischemia models, and have demonstrated benefits when administered after ischemia (Kintner et al, 2007b;Kuribayashi et al, 2000).…”
Section: Pharmacological Approachmentioning
confidence: 99%